Experience of a tertiary care center on 100 newborns with neural tube defects - Aygün, Canan; Vurucu, Sevgi; Çakmak-Çelik, Fatma; Dağçınar, Adnan; Tanyeri, Bilge; Küçüködük, Şükrü (The Turkish Journal of Pediatrics, 2013)
The aim of this study was to analyze the sociodemographic features, postoperative complications, long-term problems, and cost of care of patients followed in the neonatal intensive care unit (NICU) with a diagnosis of neural tube defects (NTDs). Babies with NTD followed in the Neonatology Unit of Ondokuz Mayıs University Faculty of Medicine between January 2003 and December 2011 were analyzed retrospectively. One hundred (1.2%) of 8408 babies admitted to the NICU were diagnosed as NTD during the study period. Of the cases with NTD, 74% of mothers were graduates of primary school/illiterate, and none had used folic acid (FA) preconceptionally. Prenatal diagnosis was made in 72%, but parents had chosen not to terminate the pregnancy. The most frequent type and site of NTD was meningomyelocele (82%) of the lumbosacral region (36%). In 80% of the babies, the NTD sac was closed with in the first 72 hours of life. The most frequently observed postoperative complications were wound infection and septicemia. The mortality rate of babies with NTD during the follow-up period was 7%, and all deaths occurred in the first year of life. Sixty-two percent of the patients had neurologic deficits on follow-up. Patients were rehospitalized during the follow-up for an average of 2.9 times. Neural tube defect (NTD) is a disabling problem, with operations, rehospitalizations and other costly treatments. Maternal education regarding preconceptional FA use/fortification of food with FA and appropriate guidance to the family with prenatal diagnosis will decrease the incidence and burden of the disease.